Perceptions of unmet needs for community social care services in England. A comparison of working carers and the people they care for. (24th January 2016) - Brimblecombe, Nicola; Pickard, Linda; King, Derek; Knapp, Martin
Abstract: Previous UK research has found expressed unmet need for services by unpaid working carers and among disabled and older people. There are, however, suggestions from research that views on unmet needs for services differ between carers and care‐recipients. Working carers in the UK say that the care‐recipient is sometimes reluctant to accept services and the few international comparative dyad studies that have been carried out find that carers perceive higher unmet need than care‐recipients. Recent policy discussions in England have also recognised that there may be differences of opinion. We collected data in 2013 from working carer/care‐recipient dyads in England about perceived need for services for the care‐recipient, disability, unpaid care hour provision and individual and socio‐demographic characteristics. We find that care‐recipients as well as their carers perceive high unmet need for services, although carers perceive higher unmet need. For carers, unmet need is associated with the disability of the carer‐recipient and being the daughter or son of the care‐recipient; for care‐recipients it is associated with unpaid care hours, carers' employment status and carers' health. The majority of dyads agree on need for services, and agreement is higher when the working carer provides care for 10 hours or more hours a week. Services for care‐recipients may enable working carers to remain in employment so agreement on needs for services supports the implementation of legislation, policy and practice that has a duty to, or aims to, support carer's employment.